Determinación del error de tipo en delitos sexuales para eximir la responsabilidad de la persona procesada - Morocho Guillen, Luis Fernando (2022)
The present thesis entitled: “DETERMINATION OF THE TYPE ERROR IN SEX CRIMES TO EXEMPT THE RESPONSIBILITY OF THE PROSECUTED PERSON”. This study arises from the need to analyze the indexes in sexual crimes emphasizing the sexual violations produced to minors, due to the exercise of sexual liberties that they maintain when having sexual relations with their sentimental partners, which results as a judicial process for an alleged fact of rape, since the victims are minors and do not have developed the necessary maturity to be able to carry out diverse acts as their parents emphasize. Therefore, a problem is evidenced before the lack of application of the constitutional norm on sexual liberties, consequently, both the defendant and the victim might become affected by not considering the consent on the part of the person concerned, and the error or ignorance on the part of the defendant by not knowing the chronological age of the affected person when the alleged fact was maintained. This fact plays a vital part to clarify the commission of the crime as a penal norm of the error of type to foresee the unlawfulness of their behavior as it is stated by the organic integral penal code. Thus, for the execution of the research, use was made of the scientific, inductive, deductive, analytical, synthetic and statistical method; with the intention of carrying out a study to know those basic concepts that will allow understanding the research topic, establishing an opinion about sexual crimes and the actions to determine a viable solution to the problem that occurs. Consequently, the results obtained allowed to determine actions that contribute to the effective development of rights, through a legal proposal that generates actions for the transformation and active exercise of the rights established in the Constitution.